2019
DOI: 10.33795/j-adbis.v13i1.67
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Store Atmosphere Terhadap Keputusan Pembelian Dan Dampaknya Terhadap Loyalitas Pelanggan Toko Buku Togamas Malang

Abstract: The main objectives of this study are: a. To find out and analyze the significant influence between store atmosphere on Purchasing Decisions. B. To find out and analyze the significant influence between store atmosphere on Customer Loyalty through Purchasing Decisions. The research location is in the city of Malang, while the study population is all customers who have studied in the TogaMas store in the last three months, while the sample is one hundred. The results showed that the data used were v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Service quality has become the major driving factor for loyalty model found in Indonesia (Albari and Kartikasari, 2019; Furoida and Maftukhah, 2018; Palit et al , 2016), Malaysia (Majid et al , 2018), Myanmar (Myo et al , 2019), Thailand (Dhasan and Aryupong, 2019) and Australia (Ponirin et al , 2011). However some studies found store atmosphere has the major rule in loyalty model such as in several cities in Indonesia which are Bandung (Alfin and Nurdin, 2017), Surabaya (Listiono and Sugiarto, 2015), Malang (Samboro et al , 2019) and Turkey (Emir, 2016). In addition, price also found in some studies as the major role in loyalty model such as in Indonesia (Budiastari, 2016), Iran (Haghighi, 2012), Kenya (Githiri, 2018) and Turkey (Cakici et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Service quality has become the major driving factor for loyalty model found in Indonesia (Albari and Kartikasari, 2019; Furoida and Maftukhah, 2018; Palit et al , 2016), Malaysia (Majid et al , 2018), Myanmar (Myo et al , 2019), Thailand (Dhasan and Aryupong, 2019) and Australia (Ponirin et al , 2011). However some studies found store atmosphere has the major rule in loyalty model such as in several cities in Indonesia which are Bandung (Alfin and Nurdin, 2017), Surabaya (Listiono and Sugiarto, 2015), Malang (Samboro et al , 2019) and Turkey (Emir, 2016). In addition, price also found in some studies as the major role in loyalty model such as in Indonesia (Budiastari, 2016), Iran (Haghighi, 2012), Kenya (Githiri, 2018) and Turkey (Cakici et al , 2019).…”
Section: Introductionmentioning
confidence: 99%